Pengaruh Metode Just In Time Terhadap Efesiensi Biaya dengan Sistem Informasi Akuntansi sebagai Variabel Intervening : Just in time, efesiensi biaya, sistem informasi akuntansi - Najmudin; Mohamad Husni; Puspita Maelani (Account : Jurnal Akuntansi, Keuangan dan Perbankan, 2022)
This research is motivated by the condition of PT. Gasbumi Sarana Karya related to JIT which is still not optimal in its production process, and the use of accounting that is still manual, so that it is less efficient in production costs and slows down decision making. The purpose of this study is to test whether there is an effect between JIT on cost efficiency with accounting information systems as an intervening variable. The research method uses quantitative methods, through data collection techniques with questionnaires distributed directly to employees at PT. Gasbumi Sarana Karya. The statistical test tool used in this research is Smart PLS. The results of this study indicate that Just in time has a significant positive effect on cost efficiency. Accounting information systems have a significant positive effect on cost efficiency. time and cost efficiency Keywords: just in time, accounting information system, cost efficiency.